5. The Myth of the "Exclusivist" Voice - the Diversity of Sound Aspects. Case Study - Gârlea Mihaela Loredana (Sciendo, 2023)
There is always talk about the voice intended exclusively for a certain musical genre. There are singing teachers who systematically refuse to encourage young voices to discover other areas of sound from the perspective of vocal practice. For example, Classical Singing teachers approach the phrase "you can't" or, worse, "you're not allowed", when a student studying Academic Singing wants to discover other musical genres such as Folk Singing, Light Music or Jazz. This obtuseness shown by some teachers leads to the premature inhibition of the singer's vocal potential in the full period of accumulation, but, above all, leads to the narrowing of horizons and opportunities on the job market of Classical Singing graduates. Such practices should be challenged and dismantled through concrete examples where one and the same voice can interpret a diversity of musical genres, without in any way affecting the artistic act.